2023
DOI: 10.1017/jog.2023.15
|View full text |Cite
|
Sign up to set email alerts
|

Ice aprons on steep high-alpine slopes: insights from the Mont-Blanc massif, Western Alps

Abstract: Ice aprons are defined as very small ice bodies covering steep rock slopes. They have only been the subject of increased scientific interest for a few years, despite the fact that they are a condition for mountaineering and obvious elements in the high-alpine landscapes. However, very little is known about their distribution, evolution and physical characteristics. In this paper, we review the existing knowledge on ice aprons, which have almost exclusively been investigated in the Mont-Blanc massif, Western Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 117 publications
(190 reference statements)
0
5
0
Order By: Relevance
“…The center of the rock wall can be divided in two parts: the upper part and lower part. The upper part, formerly covered by an ice apron (IA hereafter, figure 2(b)), defined as small ice bodies lying on slopes >40 • (Guillet and Ravanel 2020, Kaushik et al 2022, Ravanel et al 2023, depicts a complex pattern formed by a block chaos lying on a complex substratum. The lower part shows at least three fracture sets: one very steep with a N-trend, one parallel to the sub-vertical N70 • E major faults, and one almost horizontal.…”
Section: Geographical and Geological Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…The center of the rock wall can be divided in two parts: the upper part and lower part. The upper part, formerly covered by an ice apron (IA hereafter, figure 2(b)), defined as small ice bodies lying on slopes >40 • (Guillet and Ravanel 2020, Kaushik et al 2022, Ravanel et al 2023, depicts a complex pattern formed by a block chaos lying on a complex substratum. The lower part shows at least three fracture sets: one very steep with a N-trend, one parallel to the sub-vertical N70 • E major faults, and one almost horizontal.…”
Section: Geographical and Geological Contextmentioning
confidence: 99%
“…When shrinking, glaciers and IAs free boulders and rock masses become unstable (Krautblatter et al 2013). Ravanel et al (2023) found that after the 2003 and 2015 summer heatwaves, rockfall deposits heavily accumulated at the foot of recently deglaciated areas in the MBM due to retreat of IAs. Permafrost degradation at TREF was enhanced by the reduction of the IA surface area.…”
Section: Preconditioning Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of this important ongoing activity and progress, Philip Deline has built up an internationally recognised research unit carrying out pioneering work on characteristics, processes and climate-change impacts related to the coldest, steepest, highest and logistically most challenging mountain belts. The state-of-the-art review by world-leading experts on "Ice loss from glaciers and permafrost and related slope instability in high-mountain regions" (Deline et al, 2021) as well as a continued series of unique specific publications on the topic (e.g., Ravanel and Deline, 2010;Bodin et al, 2015;Magnin et al, 2015Magnin et al, , 2017Ravanel et al, 2017Ravanel et al, , 2023 document the precious contribution accomplished by the "Chambéry team". The following thoughts are devoted to Philip in recognition of, and gratefulness for this admirable achievement.…”
Section: Introduction: Backgroundmentioning
confidence: 99%
“…The eastern margin of the north face is occupied by a cold-based hanging glacier (Pralong and Funk, 2006). It is surmounted by an ice apron (Ravanel et al, 2023). Immediately to the West is the Triangle du Tacul (3970 m a.s.l.)…”
mentioning
confidence: 99%